ECOLOGICAL BIOSEMIOSIS: A BIOSEMIOTIC READING OF CULTURE AND NATURE RELATIONSHIPS IN THE SELECTED POEMS FROM A NATIVE CLEARING AND MAN OF EARTH - Ledesma, Jan Raen Carlo M.; Pascual, Chuckberry J. (Sanata Dharma University, 2023)
This paper attempts to flesh out how the biophiliac, anthropocentric, and ethnological modes of biosemiotic representation aid in the imaging and discoursing of nature-culture relationships in the selected poems from the anthologies A Man of Earth and A Native Clearing. Capitalizing on ecocriticism, biosemiotics provide an ecological reading of the manifestations of human culture and their natural surroundings. This reading underscores how meaning-making and the intricacies of the sign system transpire in all living systems. This reading also paves the way for modeling the environment through literature highlighting the complex relations between the environment and human culture with an amplified and specialized view of the individual entities that shape and affect the environment. Using the descriptive-analytical research design and the theories of Zapf, Hoffmeyer, and Uexkull, we illustrate how the biosemiotic foregrounds of the poems speak of how sign relations project the dealings and ruptures between human-cultural activities and other natural semiotic subjects. We also underscore the perils stemming from anthropocentric players with emphasis on their cultural undertakings, the hallowed character of nature steering tragic ecology, the evolutionary fitness and adaptability of animals, ecosophy and speciesism and how these affect the biosphere and the formation of biosemiotic linkages and reciprocations.